ETIKA DALAM PEMBANGUNAN INTERNASIONAL - Silsila Asri (Andalas Journal of International Studies (AJIS), 2017)
Inequality and poverty are the impact of the unevenness of the distribution of physical and economic development outcomes. This is the result of development which ignored the moral and ethical dimension. Liberal and neo liberal system makes the factors of production mastered by a few people that contribute to inequality. People who have little ability to access resources become increasingly poor and backward. Ethics of Third World Development emerged as a critical alternative approach theory which concern with community development or empowerment community to make their life become better. Gaoulet and others of critical alternative approach suggested at least there are three basic component which are should be conceptual foundation and practical guide in understanding the development, those are sustenance, self-esteem, and freedom.Key Words : Ethics of Third World Development, Sustenance, Self Esteem, Freedom